Characterization of a new anellovirus species infecting an ocelot (Leopardus pardalis) in Brazil - Liliane T. F. Cavalcante; Matheus A. C. Cosentino; Mirela D’arc; Filipe R. R. Moreira; Ricardo Mouta; Anderson M. Augusto; Fernando Troccoli; Marcelo A. Soares; André F. Santos (Genetics and Molecular Biology, 2023)
Abstract A complete genome of the first anellovirus infecting the wild felid Leopardus pardalis (ocelot) and a partial genome were assembled and annotated through high-throughput sequencing protocols followed by Sanger sequencing validation. The full-length virus obtained comprises 2,003 bp, while the partial genome comprises 1,224 bp. Phylogenetic analysis grouped these two sequences in two distinct clusters related to previously described Felidae anelloviruses. The ORF1 of the partial genome was identified as a new species provisionally called Torque teno ocelot virus, with 53.6% identity with its sister lineage. The complete genome was inferred as a new representative of the Torque teno felid virus 3 species, with 73.28% identity to the closest reference. This study expands known virus diversity and the host span of anelloviruses.